Enhanced room temperature ammonia response of 2D-Ti3C2Tx MXene decorated with Ni(OH)2 nanoparticles. Issue 14 (15th July 2021) - Kuang, Delin; Guo, Xuezheng; Zhu, ZeTao; Ding, Yanqiao; Sun, Xia; Wu, Zhilin; Zhang, Luwen; Zhou, Yangyang; He, Yong
Abstract: Due to the expansion of human production activities, toxic ammonia (NH3 ) is excessively released into the atmosphere, being a huge threat to human health and the natural environment. Therefore, it is of great significance to design an easy-synthesized gas-sensing material with both good room temperature sensitivity and selectivity for trace-level NH3 detection. Herein, we fabricate a chemiresistive NH3 gas sensor with enhanced performance based on Ni(OH)2 /Ti3 C2 T x hybrid materials. The Ni(OH)2 /Ti3 C2 T x hybrid materials are synthesized by an in-situ electrostatic self-assembly method. Attributed to the formation of interfacial heterojunctions and the modulation of carrier density, the Ni(OH)2 /Ti3 C2 T x hybrid sensor exhibits high response, outstanding repeatability, good selectivity and stability in low concentrations of NH3 . Moreover, the Ni(OH)2 /Ti3 C2 T x hybrid sensor has a higher response to 10 ppm NH3 at the relative humidity of 40% and 60%, which makes it promising for applications in real complex environments with high humidity. Benefitting from the low power consumption and easy fabrication process, the Ni(OH)2 /Ti3 C2 T x hybrid sensor possesses a broad application prospect in the internet of things (IoT) environmental monitoring.